Biblical Hebrew in context: essays in Semitics and Old Testament texts in honour of Professor Jan P. Lettinga - Bekkum, Koert van; Kwakkel, Gert; Rose, Wolter; Lettinga, Jan P. (Oudtestamentische studie͏̈n, 2018)
"For half a century Jan P. Lettinga (1921), Professor emeritus of Semitic Languages at the Theological University Kampen (Broederweg), greatly influenced the teaching of Biblical Hebrew in the Faculties of Theology, Religious Studies and Semitic Languages in the Netherlands and Belgium by his widely used grammar. This volume honours his legacy and reputation as a Semitist. Lettinga always asked how a historical approach of the Semitic languages and literature would contribute to their understanding, and how this elucidates our reading of the Hebrew Scriptures. Biblical Hebrew in Context applies this approach to issues reflecting the full breadth of Lettinga's interests: Mesopotamian and Biblical Law, the history, grammar and teaching of Hebrew and Aramaic, and the translation and interpretation of Ugaritic and Old Testament texts."--